Case Report: Bezoar in allograft duodenum—rare cause of bowel obstruction 13 years post-pancreas transplant - Urvater, Marlena; Ianiro, Cora; Bruce, David S.; Jensen, Tuesday; Finger, Erik B.; Barr, Justin (Frontiers in Transplantation, 2026)
Small bowel obstruction (SBO) following pancreatic transplantation is a recognized complication, most often caused by adhesive disease and hernias. To our knowledge, a pancreatic allograft duodenal bezoar has not been previously described as a cause of obstruction. A 69-year-old female presented to the emergency department (ED) with severe abdominal pain and computed tomography (CT) findings concerning for a SBO. Given imaging characteristics concerning for a mass and her complete obstruction, we performed an immediate exploratory laparotomy. Intraoperatively, a large, solidified bezoar within the pancreatic allograft duodenum and a smaller bezoar causing a SBO in the efferent jejunal limb were removed. This case reveals a previously undescribed cause of life-threatening obstruction within a pancreaticoduodenal allograft and highlights the importance of considering rare entities in pancreas transplant patients to preserve graft function and prevent further complications.